2021
DOI: 10.1097/md.0000000000023469
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized controlled trial of massage in children with pediatric cerebral palsy

Abstract: Background: Cerebral palsy is 1 of the diseases critically affecting the health of children. The spasmodic type is the most common, characterized by the increased muscular tension. It often leads to lifelong disability, bringing a heavy economic burden to families and society. As a key treatment in traditional Chinese medicine, pediatric massage has a significant clinical effect on cerebral palsy in children; however, high-quality randomized controlled studies are lacking. The main objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…The child will be placed in the supine position; the doctor will stand on the head side, opening the Tianmen 30 times, separate‐pushing the Kangong 30 times, separate‐pushing Ying Xiang (LI20) 30 times, kneading Taiyang (EX‐HN5) for 1 min, and grasping Jianjing (GB21) 3 to 5 times (Fig. 2).” 63 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The child will be placed in the supine position; the doctor will stand on the head side, opening the Tianmen 30 times, separate‐pushing the Kangong 30 times, separate‐pushing Ying Xiang (LI20) 30 times, kneading Taiyang (EX‐HN5) for 1 min, and grasping Jianjing (GB21) 3 to 5 times (Fig. 2).” 63 …”
Section: Resultsmentioning
confidence: 99%
“…Skin lesions and rashes are common side effects of massage. Once the AEs occur during the treatment, the time and severity of the treatment will be recorded in detail, the cause will be analysed, and the correlation between the AE and trial will be evaluated.” 63 “Expression of worsening symptoms during the study period, such as increasing pain intensity, swelling, and bruises, in which case a referral to conventional medicine would be given.” 83 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric tuina, also called pediatric anmo or traditional Chinese medicine (TCM) pediatric massage, is a special massage therapy for infants and children. Previous studies have attempted to explore the effects of pediatric tuina on numerous clinical conditions and diseases [ 11 ], such as diarrhea [ 12 ], anorexia [ 13 ], torticollis [ 14 ], cerebral palsy [ 15 ], scleroderma [ 16 ], constipation [ 17 ], infantile malnutrition [ 18 ], and fever [ 19 ] and in the promotion of the growth and development of healthy children in China [ 20 ]. Pediatric tunia is an external therapy involving the stimulation of specific areas or acupoints of the body through various manipulation techniques, such as pushing, kneading, pressing, rotating, nipping, circular, and pounding [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is an external therapy to stimulate speci c areas or acupoints of the body through various manipulation techniques, such as pushing, kneading, pressing, rotating, nipping, circular, ponding, and so forth (15,16). Previous studies have suggested that pediatric tuina may have bene cial effects on many clinical conditions and diseases (17), such as diarrhea (18), anorexia (19), torticollis (20), cerebral palsy (21), scleroderma (22), constipation (23), infantile malnutrition (24), and fever (25). Besides, tuina has been widely used to promote the growth and development of healthy children in the Chinese culture (15).…”
Section: Introductionmentioning
confidence: 99%